The Effect of Business Perceptions, Accounting Knowledge, And Business Experience on The Use Of Accounting Information on MSMEs In Grobogan District - Afifah, Zainul; Mustofa, Rochman Hadi (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the effect of perceptions of business actors, accounting knowledge, and business experience on the use of accounting information in SMEs in Ngaringan District, Grobogan Regency. Respondents in this study were MSME actors registered with the SME Cooperative Service in Grobogan Regency; as many as 253 respondents were MSMEs who had used accounting information. Collecting data using a Likert scale questionnaire. The sampling technique used is proportional random sampling. Analysis of the data used in this research is data instrument test (validity test and reliability test), assumption test (normality test, linearity test, multi collinearity test, and heterodastisity test), multiple linear regression analysis, and hypothesis testing (coefficient of determination, t-test, and test f) which is assisted by the SPSS version 25 application program. The results show that simultaneously the perceptions of business actors, accounting knowledge, and business experience together have a significant effect on the use of accounting information on MSMEs in Grobogan Regency. While the partial test of the perception of business actors, accounting knowledge, and business experience has a significant effect on the use of accounting information on MSMEs in Grobogan Regency. Among the independent variables, only the business experience variable has a not too considerable influence on the use of accounting information.